Real-world clinical outcomes with enasidenib in relapsed or refractory acute myeloid leukemia. (November 2022) - Klink, Andrew J.; Gajra, Ajeet; Knoth, Russell L.; Marshall, Landon; Hou, Ying; McBride, Ali; Copher, Ronda
Abstract: Enasidenib was approved by the Food and Drug Administration in 2017 for the treatment of patients with relapsed or refractory (RR) acute myeloid leukemia (AML) with an isocitrate dehydrogenase-2 (IDH2) mutation. Given limited data in clinical practice, this study assessed real-world clinical outcomes and healthcare resource use in patients with RR AML. Physicians performed chart abstraction of patients with RR IDH2-mutated AML treated with enasidenib (between 1/2018 and 6/2019) or other first-line (1 L) RR therapy (between 1/2016 and 7/2017). Progression-free survival (PFS) and overall survival (OS) were estimated by the Kaplan-Meier method, and adjusted risk of progression and death were estimated by multivariable Cox proportional hazard models. Among 124 patients treated with enasidenib and 76 patients treated with other 1 L RR therapy, overall response rate was higher among patients treated with enasidenib vs. other 1 L RR therapies (77% vs. 52%, p < 0.01). After a median follow-up of 9 and 6 months, median PFS was 8 months in enasidenib-treated patients and 5 months in patients receiving other 1 L RR therapy, respectively (adjusted HR=0.36, 95% CI: 0.23–0.57, p < 0.01). Median OS was 11 and 6 months in enasidenib-treated patients and patients receiving other 1 L RR therapy, respectively (adjusted HR=0.37, 95% CI: 0.22–0.60, p < 0.01). Fewer enasidenib-treated patients were hospitalized during 1 L RR therapy vs. those receiving other therapies (14% vs. 46%, p < 0.01). Results from this real-world study confirm the effectiveness of enasidenib among patients with IDH2-mutated RR AML and demonstrate that hospitalizations were significantly lower vs. other 1 L RR treatment in clinical practice. Highlights: Enasidenib had greater overall response vs other therapies in RR AML. Enasidenib had improved survival vs other therapies in RR AML. Fewer patients treated with enasidenib vs other therapies had hospitalizations.